Epithermal Gold Mineralization in the Trenggalek District, East Java, Indonesia. Issue 2 (April 2014) - Takahashi, Ryohei; Shingo, Yuki; Imai, Akira; Watanabe, Koichiro; Harijoko, Agung; Warmada, I Wayan; Idrus, Arifudin; Setijadji, Lucas Donny; Phoumephone, Phouvang; Scherstén, Anders; Page, Laurence
Abstract: Gold‐mineralized quartz veins at the Trenggalek district of the Southern Mountains Range in East Java, Indonesia, are hosted by Oligo‐Miocene volcaniclastic and volcanic rocks, and are distributed close to andesitic plugs in the northern prospects (Dalangturu, Suruh, Jati, Gregah, Jombok, Salak, and Kojan) and the southern prospects (Sentul and Buluroto). The plugs are subalkaline tholeiitic basaltic‐andesite to calc‐alkaline andesite in composition. 40 Ar– 39 Ar dating of a quartz‐adularia vein at the Dalangturu prospect yielded an age of 16.29 ± 0.56 Ma (2σ), and a crystal tuff of a limestone‐pyroclastic rock sequence at the southwest of the Dalangturu prospect was determined as 15.6 ± 0.5 Ma (2σ). Statistic overlap of ages suggests that the gold mineralization in the northern prospects took place in a shallow marine to subaerial transitional environment. Hydrothermal alteration of the host rocks is characterized by the replacement of quartz, illite and adularia. Quartz veins in surface outcrops are up to 50 cm wide in the northern prospects and up to 3 m wide in the southern prospects, showing a banded or brecciated texture, and are composed of quartz, adularia, carbonates with pyrite, electrum, sphalerite, galena, and polybasite. Gold contents of quartz veins are positively correlated with Ag, Zn, Pb, and Cu contents in both the northern and southern prospects. The quartz veins at the Jati, Gregah, and Sentul prospects have relatively lower gold‐silver ratios (Ag/Au = 23.2) compared to those at the Kojan, Dalangturu, Salak, and Suruh prospects (Ag/Au = 66.8). The quartz veins at the Dalangturu prospect are relatively rich in base metal sulfides. Ag/(Au+Ag) ratios of electrum in the Dalangturu prospect range from 45.2 to 65.0 at%, and FeS contents of sphalerite range from 1.2 to 6.4 mol%. Fluid inclusion microthermometry indicates ore‐forming temperatures of 190–200°C and 220–230°C at the Sentul and Kojan prospects, respectively. Widely variable vapor/liquid ratio of fluid inclusions indicates that fluid boiling took place within the hydrothermal system at the Sentul prospect. Salinities of ore‐fluids range from 0 to 0.7 wt% (av. 0.4 wt% NaCl equiv.) and from 0.5 to 1.4 wt% (av. 0.9 wt%) for the Sentul and Kojan prospects, respectively. The boiling of hydrothermal fluid was one of the gold deposition mechanisms in the Sentul prospect. Abstract : Several epithermal gold‐vein prospects were identified at the Trenggalek district of the Southern Mountains Range in East Java, Indonesia. The veins are hosted by Oligo‐Miocene volcaniclastic and volcanic rocks. We describe occurrences of the gold mineralization and related igneous rocks and present an ore‐forming condition based on age dating, microscopic observation, bulk chemical composition analysis, mineral chemistry, fluid inclusion microthermometry and thermodynamic calculations.